Analysis of Emergency Preparedness and Response Procedures in The State on Fire at PT Gold Coin Indonesia: Analisis Prosedur Emergency Preparedness and Response (EPR) Sebagai Upaya Pengendalian Keadaan Darurat pada Keadaan Kebakaran di PT Gold Coin Indonesia - M. Alfin Sukma Santoso; Rizqi Novita Sari (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
This study aims to analyze the implementation of Emergency Preparedness and Response (EPR) in controlling fire emergencies at PT Gold Coin Indonesia, a livestock feed manufacturing company. This study evaluates the company's readiness to deal with potential emergencies through operational procedures, equipment provision, training, and simulations. Data were collected through field observations, interviews with the emergency response team, and review of related documents. The results of the analysis show that the company has integrated EPR into the Occupational Safety and Health Management System (SMK3) since 2018, including emergency response procedures, training, and equipment maintenance. However, challenges were found in the limited number of light fire extinguishers (APAR) and the frequency of simulations that still need to be improved. The results of this analysis provide recommendations for improving safety facilities, optimizing training, and strengthening cooperation with external parties. These findings are expected to support the development of more effective occupational safety policies.